Placental steroid sulphatase deficiency: an approach to antenatal care and delivery - Frieda-Elsje Dreyer; Ganiy Opeyemi Abdulrahman; Gareth Waring; Kim Hinshaw (Annals of Saudi Medicine, 2018)
Placental steroid sulphatase deficiency (SSD) is an X-linked inborn error of metabolism. Congenital X-linked ichthyosis (XLI) is a genetic disorder of keratinisation caused by steroid sulphatase (STS) deficiency, which results in a scaling skin condition in male infants shortly after birth. It may be associated with failed induction of labor and prolonged labor leading to cesarean delivery due to ‘cervical dystocia’. We present two cases of congenital ichthyosis. Thorough counselling of women with a previously affected pregnancy during the antenatal period should include discussion about mode of delivery and a critical review of the complexities of prenatal diagnosis in this condition. We propose a clinical management pathway to offer women with a previous pregnancy affected by this rare condition. SIMILAR CASES PUBLISHED: Less than 50 cases reported. CONFLICT OF INTEREST: None.